2013
DOI: 10.1002/esp.3505
|View full text |Cite
|
Sign up to set email alerts
|

Depth and character of rock weathering across a basaltic‐hosted climosequence on Hawai‘i

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. The transport of organic carbon (C) to deep mineral horizons in soils can lead to long-term C stabilization. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
57
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 80 publications
(144 reference statements)
0
57
0
Order By: Relevance
“…However, with between 700 and 1200 mm/yr precipitation, the thickness of the weathering zone varied between 6 and 40 m. It was only for annual precipitation >1300 mm that weathering zones exceeded 45 m thickness. Chadwick et al (2003) and Goodfellow et al (2014) noted similar precipitation thresholds at 1400 mm/yr and 1200 mm/yr, respectively, albeit on the much younger Kohala lavas.…”
Section: Mineralogy Of Hawaiian Lateritesmentioning
confidence: 76%
See 1 more Smart Citation
“…However, with between 700 and 1200 mm/yr precipitation, the thickness of the weathering zone varied between 6 and 40 m. It was only for annual precipitation >1300 mm that weathering zones exceeded 45 m thickness. Chadwick et al (2003) and Goodfellow et al (2014) noted similar precipitation thresholds at 1400 mm/yr and 1200 mm/yr, respectively, albeit on the much younger Kohala lavas.…”
Section: Mineralogy Of Hawaiian Lateritesmentioning
confidence: 76%
“…1), wetter than the ~1400 mm/yr threshold for thick and thorough leaching of bedrock on the Kohala Peninsula (Chadwick et al, 2003;Goodfellow et al, 2014). The area is heavily vegetated, such that soil CO 2 concentrations are undoubtedly high and help drive weathering reactions through the formation of carbonic acid in soil waters.…”
Section: Geologic and Hydrologic Settingmentioning
confidence: 99%
“…Elevation gradients encompass a range of precipitation and temperature across short distances and record climate effects on soil development and weathering (e.g., Koch et al, 1995;Dahlgren et al, 1997;Bockheim et al, 2000;Egli et al, 2003;Stiles et al, 2003;Goodfellow et al, 2014). Similarly, soil profiles observed across latitudinal gradients (Muhs et al, 2001;Williams et al, 2010) or at a variety of latitudes (Rasmussen et al, 2011) show correlations of climate to weathering rates and mineral transformations.…”
mentioning
confidence: 99%
“…In landscapes where physical erosion is low, studies at multiple spatial scales have demonstrated that precipitation and temperature strongly control chemical weathering rates and soil development when all other state factors are held constant (Strakhov, 1967;Ruhe, 1984;Chadwick et al, 2003;Dahlgren et al, 1997;Rasmussen et al, 2007;Williams et al, 2010;Goodfellow et al, 2014). The degree of soil development varies considerably with changes in climate, with thresholds observed in weathering processes and soil formation between water-limited systems and energy-limited systems (Dahlgren et al, 1997;Rasmussen et al, 2011;Goodfellow et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation